Aminopeptidase Substrate Preference Affects HIV Epitope Presentation and Predicts Immune Escape Patterns in HIV-Infected Individuals - Zhang, Shao Chong; Martin, Eric; Shimada, Mariko; Godfrey, Sasha Blue; Fricke, Jennifer; Locastro, Shirley; Lai, Nicole Y; Liebesny, Paul; Carlson, Jonathan M.; Brumme, Chanson J; Ogbechie, Oluwatobi Awele; Chen, Huabiao; et al. (The Journal of Immunology, 2012)
Viruses evade immune detection partly through immune-associated mutations. Analyses of HIV sequences derived from infected individuals have identified numerous examples of HLA-associated mutations within or adjacent to T cell epitopes, but the potential impact of most mutations on epitope production and presentation remains unclear. The multistep breakdown of proteins into epitopes includes trimming of N-extended peptides into epitopes by aminopeptidases before loading onto MHC class I molecules. Definition of sequence signatures that modulate epitope production would lead to a better understanding of factors driving viral evolution and immune escape at the population level. In this study, we identified cytosolic aminopeptidases cleavage preferences in primary cells and its impact on HIV Ag degradation into epitopes in primary human cell extracts by mass spectrometry and on epitope presentation to CTL. We observed a hierarchy of preferred amino acid cleavage by cytosolic aminopeptidases. We demonstrated that flanking mutations producing more or less cleavable motifs can increase or decrease epitope production and presentation by up to 14-fold. We found that the efficiency of epitope production correlates with cleavability of flanking residues. These in vitro findings were supported by in vivo population-level analyses of clinically derived viral sequences from 1134 antiretroviral-naive HIV-infected individuals: HLA-associated mutations immune pressures drove the selection of residues that are less cleavable by aminopeptidases predominantly at N-flanking sites, leading to reduced epitope production and immune recognition. These results underscore an important and widespread role of Ag processing mutations in HIV immune escape and identify molecular mechanisms underlying impaired epitope presentation.